2019
DOI: 10.1186/s12886-018-1024-7
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pediatric ocular injuries based on intention in patients admitted with trauma

Abstract: PurposePediatric ocular trauma is a major source of morbidity and blindness and the number of epidemiological studies is incommensurate with its significance. We sought to determine differences in epidemiologic patterns of pediatric ocular injuries based on intention.MethodsA retrospective review of the National Trauma Data Bank (2008–2014) was performed and patients < 21 years old, admitted with trauma and ocular injury, were identified using ICD-9CM codes. Demographic data, types of injury and external circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
3
0
1
Order By: Relevance
“…Our study confirmed previously reported findings that firearms and self-inflicted injuries were associated with more severe injury indices and thus mortality [ 19 , 36 , 37 ]. Cut/piece injuries have lower severity indices and lower mortality.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study confirmed previously reported findings that firearms and self-inflicted injuries were associated with more severe injury indices and thus mortality [ 19 , 36 , 37 ]. Cut/piece injuries have lower severity indices and lower mortality.…”
Section: Discussionsupporting
confidence: 92%
“…These children had 8.5 times higher odds of mortality than other intentions. This study found that firearms were the most likely mechanism [ 19 ]. Other trauma investigators have reported similarly high injury severity and mortality rates with self-inflicted trauma than other intentions [ 41 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complete removal of residual organic IOFBs is crucial to prevent infections and inflammation. 32 The research describes an uncommon and intriguing case involving a pediatric patient with an intraorbital foreign body (IOFB) that penetrated the orbital cavity and extended into the temporal lobe. Medical terminology is used appropriately, balancing technical details with readability.…”
Section: Discussionmentioning
confidence: 99%
“…A morte infantil, em muitos casos, não se deve a uma única causa, mas a uma complexa soma de fatores de risco. A qualidade, a disponibilidade e o acesso aos cuidados em saúde são aspectos importantes que podem influenciar não apenas a probabilidade de sobreviver a uma lesão, mas, também, as consequências em longo prazo [4][5][6] . Programas de prevenção que levam em consideração vulnerabilidades e usam uma abordagem multidisciplinar têm se mostrado os mais eficazes para reduzir a mortalidade infantil como resultado de uma lesão 7 .…”
unclassified